FUNGSI PEMERINTAH KELURAHAN DAN LEMBAGA PEMBERDAYAAN MASYARAKAT DALAM PEMBANGUNAN DI KELURAHAN LASIANA DAN KELURAHAN OESAPA KECAMATAN KELAPA LIMA KOTA KUPANG - Mooy, Fiona Bellania; Monteiro, Yosef Mario; Ratu Udju, Hernimus (Petitum Law Journal, 2024)
The role of the Subdistrict Government and Community Empowerment Institutions in the context of community economic development is very important in efforts to improve community welfare. The provisions of Article 5 of the Kupang City Regional Regulation Number 9 of 2016 concerning Village Community Institutions state that; LPM is a partner of the Government in developing the community's economy, but the implementation level is still considered not optimal. This research is empirical legal research. The results of the research found that: (a) Development programs in the Oesapa subdistrict that have been running, namely: Development of Oesapa Market Stall Infrastructure, direct cash assistance, small and medium enterprises and revolving activities that have been implemented amounting to Rp. 835. 750,000 while the Development Program in Lasiana sub-district is the Stunting Program, Environmental Cleanliness, Independent Credit Work Program and revolving funds to support community economic growth amounting to Rp. 658,000,000; (b) Things that hinder development at the Oesapa subdistrict office and the Lasiana subdistrict office are: available budget cannot reach all community development needs, coordination in the implementation of activities in Lasiana and Oesapa subdistricts and coordination in the implementation of development work programs requires coordination between all related parties in order to minimize program errors and failures; (c.) Socialization requires regular and ongoing socialization so that it can be utilized by the community; and (d.) the available infrastructure is inadequate and needs to be improved.